Do Different Types of Intelligence and Its Implicit Theories Vary Based on Gender and Grade Level? - Ayoub, Alaa Eldin A.; Aljughaiman, Abdullah M.; Alabbasi, Ahmed M. Abdulla; Abo Hamza, Eid G. (Frontiers in Psychology, 2022)
The current study investigated correlations among gifted students’ academic performance; emotional, social, analytical, creative, and practical intelligence; and their implicit theories of intelligence. Furthermore, it studied the effect of gender and grade on these variables. The participants included 174 gifted fifth (41.4%) and sixth (58.6%) grade students, comprising 53.4% male and 46.6% female. The following analytical, creative, and practical intelligence tests were administered: Aurora Battery, the emotional intelligence scale, the implicit theories of intelligence scale, and an assessment scale of students’ performances. The results revealed significant correlations among academic performance, kinds of intelligence, and implicit theories of intelligence. There were no significant differences between the male and female students in these measures. There were, however, significant differences between the fifth and sixth grade students, with the sixth-grade students showing higher levels of all kinds of intelligence, except emotional intelligence. Moreover, the results indicated that the intelligence measures were non-significantly affected by either gender or gender–grade interaction. Overall, our results showed that most types of intelligence are related to giftedness, and that there were no gender differences among gifted students on measures of intelligence.